ANALISIS PERFORMA ROUTING OSPF PADA TOPOLOGI HYBRID STAR-MESH DAN TOPOLOGI TREE MENGGUNAKAN GNS3 - Muhammad Naufal Musyaafa; Ayman Human Sukma; Sybil Auzi; Dedy Kiswanto (LPPM Universitas Dhyana Pura, 2025)
This research analyzes the performance comparison of OSPF (Open Shortest Path First) routing protocol on hybrid star-mesh topology and tree topology. Testing was conducted through simulation using GNS3 with Mikrotik routers configured with OSPF protocol. Performance parameters measured include throughput, jitter, delay, and packet loss. The results show that the hybrid star-mesh topology provides better performance, particularly in terms of delay with an average of 2.548 ms (15.46% faster compared to tree topology) and more stable jitter with an average of 3.193 ms (10.4% lower than tree topology). Meanwhile, both topologies showed relatively equivalent throughput with average values of 958 Kbits/s for hybrid star-mesh and 962.7 Kbits/s for tree, with no packet loss observed in either topology. Although the performance differences are not highly significant, the hybrid star-mesh topology proves superior in providing more responsive and consistent communication paths. This research provides comprehensive recommendations regarding the selection of optimal network topology for OSPF protocol implementation in the context of enterprise and educational network requirements.